A Physical-chemical Synergetic Inhibitor for Coal Spontaneous Combustion and Its Fire Prevention Performance. Issue 6 (26th April 2022) - Cai, Jiawen; Yang, Shengqiang; Zhong, Yan; Song, Wanxin; Zheng, Wancheng
ABSTRACT: A single physical or chemical inhibitor can hardly meet the uttermost requirements for coal spontaneous combustion prevention. Therefore, it has become essential to develop an efficient inhibitor with multiple inhibitory properties. In light of studies on the properties of the super absorbent polymer (SAP), the main antioxidant pentaerythritol tetrakys 3-(3, 5-ditert-butyl-4-hydroxyphenyl) propionate and auxiliary antioxidant tris (2, 4-di-tert-butyl-pheny) phosphite, a synergistic antioxidant with both physical and chemical inhibitory properties was prepared. According to the determination of volatile matter and calorific value of coal, the optimum molar ratio of the compound antioxidant (main antioxidant: auxiliary antioxidant = 2:1) was selected. Furthermore, the optimum formulation ratio (SAP: antioxidant = 1:3) and the optimum mass ratio (12%) were determined, taking the low-temperature oxygen consumption and cross-point temperature (CPT) of coal as indexes. Three grades of metamorphic coal were selected to obtain the gaseous product, oxygen consumption at 70°C, CPTs and inhibition rate. The addition inhibitor reduced the release of CO and C2 H4 gas and oxygen consumption, while it raised CPTs and inhibition rate of coal oxidation. The inhibiting capacity of MgCl2 is mainly at low-temperature stage, while the synergistic inhibitor has excellent congenerous physical and chemical effect in the whole coal oxidation process.